Two Forms of Exclusion Mean Two Different Negations. (17th December 2014) - Silva, Marcos
Abstract: Here, the logical behaviour of negation in Wittgenstein's Tractatus (1918) is compared with Demos' account of denial (1917). Even if we hold negation as a pure syntactical device, at least in some context, it brings a handful of complex semantic information – potentially an infinite amount (e.g., in the ascription of degrees to empirical qualities or of colours to visual points). We advocate then the existence of at least two negations due to the existence of two different and non‐reducible types of exclusion. The first negation is a Tractarian and classical one, based on the notion of contradiction, whereas the second is a non‐classical negation, based on the notion of contrariety.